Orienting our view of the superior colliculus: specializations and general functions. (December 2021) - Allen, Kathryne M.; Lawlor, Jennifer; Salles, Angeles; Moss, Cynthia F.
Abstract: The mammalian superior colliculus (SC) and its non-mammalian homolog, the optic tectum are implicated in sensorimotor transformations. Historically, emphasis on visuomotor functions of the SC has led to a popular view that it operates as an oculomotor structure rather than a more general orienting structure. In this review, we consider comparative work on the SC/optic tectum, with a particular focus on non-visual sensing and orienting, which reveals a broader perspective on SC functions and their role in species-specific behaviors. We highlight several recent studies that consider ethological context and natural behaviors to advance knowledge of the SC as a site of multi-sensory integration and motor initiation in diverse species. Highlights: The SC is a layered sensorimotor structure, and its anatomical organization is highly conserved across taxa. The SC serves broad functions in orienting behaviors, mediating prey capture, predator avoidance and navigation. The SC has a conserved function across taxa in the execution of orienting behaviors to ethologically relevant stimuli.